2007
DOI: 10.1177/0309089207083762
|View full text |Cite
|
Sign up to set email alerts
|

A New Interpretation of the Term opalim (see pdf for image) in the Light of Recent Archaeological Finds from Philistia

Abstract: In the light of recent archaeological finds from Iron Age Philistia and comparative evidence from Aegean and ancient Near Eastern cults, a new interpretation is suggested for the term opalim ( ), mentioned in the `ark narrative' (e.g. 1 Sam. 5.6; 6.5). Although most often interpreted as relating to `haemorrhoids' or the bubonic plague, it is suggested that this, in fact, is a term referring to an affliction of the Philistines' membra virile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Repeated examples of corners/installations that were dedicated for cultic/ritual functions in seemingly domestic and/or industrial contexts were found in the late Iron Age IIA destruction level at Tell es‐Safi/Gath (Zukerman and Maeir ). Various cultic objects were found in these corners, including chalices (Maeir and Shai ), phallic‐shaped situlae (Maeir ), figurines (Maeir ) and notched scapulae (Zukerman et al . 2007; 2012), the latter one of the many introduced features found at Philistine sites that continued into the late Iron Age IIA.…”
Section: Continuity In Philistine Culturementioning
confidence: 99%
“…Repeated examples of corners/installations that were dedicated for cultic/ritual functions in seemingly domestic and/or industrial contexts were found in the late Iron Age IIA destruction level at Tell es‐Safi/Gath (Zukerman and Maeir ). Various cultic objects were found in these corners, including chalices (Maeir and Shai ), phallic‐shaped situlae (Maeir ), figurines (Maeir ) and notched scapulae (Zukerman et al . 2007; 2012), the latter one of the many introduced features found at Philistine sites that continued into the late Iron Age IIA.…”
Section: Continuity In Philistine Culturementioning
confidence: 99%
“…The chaste tree also relates to the Asclepios cult in Sparta. Of note, cultic paraphernalia at Gath includes phallic-shaped situlae also found at Philistine Ashkelon, as well as in the Asclepios sanctuary at Sparta 103 . These findings further connect the Philistines with the symbolism of revivification.…”
Section: Resultsmentioning
confidence: 97%
“…While clearly these objects are of Egyptian origin and significance, one may wonder whether perchance they arrived in Ashkelon via trade rather than through the presence of Egyptian officials. In a discussion of the bronze situlae found in this assemblage, the author refers to the ceramic situlae found in Iron Age IIA Tell es Safi/Gath, but does not refer to the detailed research paper on these vessels and their interpretation (Maeir 2007), but only to a popular and partial summary of this topic (Maeir 2008).…”
mentioning
confidence: 99%